Financial Performance on Tax Aggressiveness and Board Independence as Moderating Effect in Banking Companies - Kusairi; Pujangga Abdillah (University of Merdeka Malang, 2025)
Even though there is more evidence that corporate governance plays a crucial role in influencing business behavior, little is known about how board independence affects the relationship between Financial Performance and Tax Aggressiveness in Indonesian banks from 2019 to 2024. This study looks at how board independence affects the link between Tax Aggressiveness and Financial Performance in Indonesian banks between 2019 and 2024. The effective tax rate served as a proxy for Corporate Tax Aggressiveness (CTA), whereas board independence and profitability served as proxies for Corporate Financial Performance (CFP). Data was gathered from Indonesian IDX listings. Based on the Hausman test, random effects were used to analyze the data. The study finds that compared to smaller banks, larger banks typically employ fewer CTA tactics. Additionally, boards with more independent directors typically engage in less aggressive tax-related activity. Furthermore, to increase the cash flow available for debt service, highly leveraged enterprises are more interested in minimizing taxes, according to the study's findings. Additionally, when the moderate influence of board independence is considered, the analysis finds that Board Independence strengthen between CFP and CTA. The report recommends encouraging bank management to compare their tax policies to industry norms through peer comparisons and benchmarking exercises. This can provide a more standardized and accountable approach to tax planning and assist in identifying outliers.